Advances in Schizophrenia Research 2009 - Gattaz, Wagner F.; Busatto, Geraldo. (Springer New York, 2010)
Advances in Schizophrenia Research 2009 Edited by Wagner F. Gattaz and Gerardo Busatto Schizophrenia stands as a major psychiatric mystery: devastating to patients and families, resistant to treatment, burdened by stigma, causes unknown. As interest and research in the disorder continue worldwide, new sources for comprehensive reviews of cutting-edge studies are of growing importance. The leadoff volume of Advances in Schizophrenia Research 2009 fills this need with welcome innovation and scientific rigor. Presenting papers from the recent Symposium on the Search for the Causes of Schizophrenia, leading scientists offer latest findings, promising theories, relevant controversies, and emerging frontiers, in areas as varied as commonalities with other psychotic disorders and the impact of social factors on rehabilitation. Whether ones interest is in prevalence, genetics, risk factors, neuropathology, diagnostic boundaries, or treatment options, the discussion includes a number of intriguing and informative perspectives. A sampling of the topics covered: Incidence and outcome of schizophrenia: the view from around the world. Schizophrenia: neurodevelopmental, neurodegenerative, or both? The molecular genetics and proteomics of schizophrenia. Marijuana use: distraction from the issues, or key to the disease? Antipsychotic drug treatment: facts and fiction The case for schizophrenia as cognitive disorder. This wide-ranging coverage makes Advances in Schizophrenia Research 2009 a reference for professionals in clinical psychology, psychiatry, neuropsychology and other mental health workers, promoting more nuanced understanding of the disease, providing deeper insights into its management, and inspiring new possibilities for practice and research.